Incidence of Maxillofacial Injury Among Patients Reporting to Private Dental College: A Retrospective Study - ALBERT, DYNA; MR MUTHUSEKHAR; SELVARASU, KATHIRAVAN (The journal of contemporary issues in business and government, 2021)
Maxillofacial injury often results in mortality and morbidity related to functional and esthetic compromise. In developing countries, the greatest threat to sustaining these injuries is in road traffic accidents. It is estimated that 1.3 lakh people end up in fatal death each year due to RTA. The aim of the study is to analyse the age and gender distribution of maxillofacial injuries and to find any association between the etiology of injury with age and gender. This retrospective observational study was conducted among patients reporting to the Department of oral and maxillofacial surgery in Saveetha Dental College, Chennai. Exclusion criteria was patients reporting fractures associated/ secondary to other pathologies (local or systemic), patients with debilitating systemic disease, mentally and physically challenged, patients with head or cervical spine injury. The study data were retrieved from DIAS and analysed in IBM SPSS using descriptive statistics. Among 77 samples included in the study, 85.7% were males and 14.3% were females. Maxillofacial injury was more commonly seen in the 3rd decade of life (35.1%). There was no significant association between etiology and gender and etiology and age. Maxillofacial injury is more prevalent in males in their 3rd decade of life.